Tendon transplantations for radial palsy - De la Puente, Luis (1920)
Among peripheral paralysis determined by traumatic nerve injuries, paralysis of the radial is the major disturbances originating in member functions. Disabling the diseased limb is usually more serious than that caused injury to the ulnar nerve or the median, nerves, functionally, are likely to be supplied in the territory that innervate muscle together.